Carbon balance in grapevine under a changing climate - Medrano Gil, Hipolito; Perez Peña, Jorge Esteban; Prieto, Jorge Alejandro; Tomás Mir, Magdalena; Franck, Nicolás; Escalona Lorenzo, José Mariano (2017)
The measurement of the carbon balances is necessary to evaluate the contribution of different biomes to carbon sequestration and therefore to mitigate the global climate change effects. Carbon balance of grapevine is of major interest because of the extension and wide distribution of this crop, but also to characterize its sustainability and to satisfy increasing demands about the environmental footprint of wine production. However, references accounting for the carbon balance for different grapevine genotypes and environments are scarce. Carbon balance is an integration of two key physiological processes: photosynthesis (carbon uptake) and respiration (carbon release). Both largely depend on genotype, environmental conditions and agronomic practices. Different methodologies to measure carbon balance in grapevines are summarized, together with the practical difficulties of obtaining reliable field data. On the other hand, the increasing interest of whole plant chambers to evaluate the dynamics of responses to environmental, genetic and agronomic variables is discussed.